Preparation, loading and application method of PA / CN-WO3at-delta-MnO2 composite photocatalytic material

Through the preparation and loading method of PA/CN-WO3@δ-MnO2 composite photocatalytic material, the problems of low removal efficiency and insufficient selective purification capacity in meal places are solved, and efficient, economical and selective degradation effects are achieved.

CN119549173APending Publication Date: 2025-03-04TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311055332.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing photocatalytic technology has low efficiency in removing gaseous aldehydes in meal sites, cannot selectively purify single pollutants, and ultraviolet light degradation produces by-product ozone.

Method used

PA/CN-WO3@δ-MnO2 composite photocatalytic material was used to prepare δ-MnO2, graphite phase carbon nitride and CN-WO3 composite materials by high-temperature calcining precursor material, and hygroscopic periodic acid (PA) was introduced on the catalyst to form a self-wetting layer, enhancing the photocatalytic removal ability.

Benefits of technology

It achieves more economical, efficient and selective degradation of low-concentration gaseous aldehydes in meal places, solving the problem of low efficiency of existing photocatalytic materials and the inability to selectively purify single pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549173A_ABST
    Figure CN119549173A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method, a loading method and an application method of a PA / CN-WO3at-delta-MnO2 composite photocatalytic material. The preparation method comprises the following steps: 1) preparing delta-MnO2, g-C3N4 and WO3 which are used for removing aldehydes and have an optimal crystal structure by adopting a method of calcining a manganese dioxide precursor material (MnSO4.H2O, KMnO4), a graphite phase carbon nitride precursor material (urea) and a tungsten trioxide precursor (Na2WO4) at a high temperature; and 2) stirring the precursor materials of delta-MnO2, g-C3N4 and WO3 in deionized water, washing, drying, calcining at high temperature, and adding hygroscopic periodic acid (PA) to obtain a PA / CN-WO3at-delta-MnO2 composite photocatalytic material solution provided by the invention. And (3) directly pouring the solution into a groove formed by folding the glass fiber filter membrane in a solution state, putting the solution into a continuous flow photocatalytic reactor, and purging the solution by clean air until no obvious water drop adheres to the solution. According to the method, the material can be uniformly loaded on the glass fiber filter membrane, and the problem of non-uniform manual powder coating is effectively improved. Meanwhile, the composite material shows higher photocatalytic activity, and economical and efficient degradation of gaseous low-concentration aldehydes in a special meal place is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalytic materials and specifically relates to a PA / CN-WO 3 @δ-MnO 2 Preparation, loading and application methods of composite photocatalytic materials. Background Art

[0002] During the cooking process, a large amount of volatile organic compounds and oil droplets are produced and discharged into the environment. A variety of hydrocarbons, such as alkanes, alkenes, aldehydes, aromatic hydrocarbons and ketones, have been detected in VOCs (volatile organic compounds) in cooking fumes. Among them, acetaldehyde, limonene, etc., as precursors of ozone, will produce ozone through photochemical reactions. Limonene and other alkenes will produce secondary organic aerosols under a certain concentration of ozone and photolysis, which will endanger the natural environment and human health. In terms of odor perception, aldehyde and ketone compounds are the key types of odor substances in dining places, including acetaldehyde, acetone, valeraldehyde, octanal, etc., which are the main volatiles of various foods and fumes. The olfactory thresholds of acetaldehyde, propionaldehyde, and acrolein are approximately 2.95, 2.59, and 9.01 μg / m 3 It can be seen that the olfactory threshold of aldehydes is relatively low, that is, they have a stronger odor perception ability at a lower concentration. Existing studies have also shown that aldehydes are substances with higher concentrations in dining places. In order to improve the air quality of dining places and reduce the harm of gaseous organic matter to the human body, it is necessary to study the removal of gaseous aldehydes.

[0003] By analyzing the engineering application characteristics of existing technologies, the purification technologies suitable for catering places are selected as follows: adsorption, catalytic oxidation, photocatalysis, and ozone oxidation. Photocatalysis technology is considered the preferred technology for low-concentration gas purification because it is suitable for low-concentration gas purification with small flow rates and can operate under mild conditions. However, this technology also has its own application limitations, such as low efficiency; UV degradation produces ozone as a byproduct; and it is unable to selectively purify a single pollutant.

[0004] To address the problems of low efficiency and inability to selectively purify a single pollutant, the main improvement ideas are:

[0005] 1) Manganese oxide, which can efficiently remove low-concentration aldehydes at room temperature, was used as the research substrate. The existing purification studies of acetaldehyde, acetone, valeraldehyde, octanal, etc. have large differences among experiments, and it is impossible to systematically compare the advantages and disadvantages of various substrates. Therefore, when selecting substrates, we mainly refer to the existing more mature formaldehyde purification studies. Different metal oxides have different reactivity with aldehydes. Among them, Ag 2 O, PdO, CoO, MnO 2 、TiO 2 、CeO 2 and Mn3 O 4 The removal rate of formaldehyde (HCHO) is higher than 50%. 2 O 3 , ZnO and V 2 O 5 There was no reaction under these conditions. MnO 2 The reaction activity to HCHO is the highest, and MnO x With different crystal structures, such as α, β, γ, λ, δ and ε-MnO x , which can significantly affect the catalytic activity; the external electronic structure of Mn is 3d 5 4s 2 , with multiple valence states from -3 to +7, so MnO x Electrons can be regulated to produce the mobile electron environment required for redox reactions; MnO x Doping with other transition metal oxides produces a synergistic effect and can significantly increase the oxygen vacancies with strong redox properties.

[0006] 2) Selectively generate key active oxygen species for removing aldehydes. The principle of generating free radicals in the photocatalytic process is that when light with energy greater than or equal to the energy gap is irradiated onto the catalyst surface, the electrons in its valence band will be excited to jump to the conduction band, leaving relatively stable holes in the valence band, thus forming electron-hole pairs. The holes in the valence band can react with H adsorbed on the surface. 2 O or hydroxyl radicals to produce hydroxyl radicals (·OH). The electrons in the conduction band can react with O 2 Combined to generate superoxide radicals (·O 2 - ). The conduction band (CB) edge ratio is 2 / ·O 2 - Semiconductors with more negative potential can transfer photoactivated electrons to the π* orbitals of oxygen molecules, thereby generating superoxide radicals. 3 N 4 The hole (h + ) is insufficient to oxidize H 2 O generates ·OH, and the relatively negative conduction band (CB) position is thermodynamically capable of reducing O 2 Formation O 2 - So I chose gC 3 N 4 As one of the composite substrates.

[0007] 3) Based on the hydrophilicity of aldehydes, PA is used to construct a self-wetting layer. Hygroscopic periodic acid (PA) introduces an in-situ water layer (self-wetting layer) on the catalyst to enhance the photocatalytic removal of hydrophilic VOCs in the air. In the ambient air, water vapor condenses on the CN-WO 3 @@δ-MnO 2 A unique three-phase (air / water / CWM) system is formed on the surface of the CWM. The in-situ formed water layer can selectively concentrate hydrophilic VOCs.

[0008] Under the above technical background, a PA / CN-WO is proposed. 3 @δ-MnO 2 The preparation, loading and application methods of composite photocatalytic materials are suitable for selective removal of gaseous aldehydes in a specific place such as a dining place. Summary of the invention

[0009] The present invention aims to solve at least one of the technical problems existing in the existing ultraviolet photocatalytic technology and provide a PA / CN-WO 3 @δ-MnO 2 The preparation, loading and application methods of composite photocatalytic materials are suitable for selective removal of gaseous aldehydes in a specific place such as a dining place.

[0010] To achieve the above object, the present invention adopts the following technical solution:

[0011] A PA / CN-WO 3 @δ-MnO 2 A method for preparing a composite photocatalytic material comprises the following steps:

[0012] 1)δ-MnO 2 Preparation: The manganese dioxide precursor material (MnSO 4 ·H 2 O, KMnO 4 ) method to prepare the optimal crystal structure for removing gaseous aldehydes in manganese dioxide.

[0013] 2) Preparation of graphite carbon nitride: gC is prepared by calcining the precursor material (urea or melamine) at 500-550°C for 1.5-2.5h. 3 N 4 .

[0014] 3) CN-WO 3 Preparation: Mix the precursor materials sodium tungstate or ammonium tungstate with urea and calcine at 500-550°C for 3-6 hours.

[0015] 4) CN-WO 3 @δ-MnO 2Preparation: 70mg~3.5gCN-WO 3 54mg~2.7g KMnO 4 , 10mg~500mgMnSO 4 ·H 2 O is mixed in 5-30 mL of deionized water, and magnetically stirred at 30° C. for 60-90 minutes; dried at 120-200° C. for 8-16 hours; washed by centrifugation with water and anhydrous ethanol for 3-5 times respectively; the product is placed in a vacuum drying oven and dried at 60-100° C. for 12-14 hours; the product is heated from room temperature to 320-370° C. at a heating rate of 9-11° C. / min, and the temperature is maintained for calcination for 2.5-4 hours.

[0016] 5) PA / CN-WO 3 @δ-MnO 2 Preparation: 10mg~0.25g CN-WO 3 @δ-MnO 2 Add 1-10 ml of 4-10 wt% PA solution and 5-30 mL of deionized water, and stir magnetically at 30° C. for 60-90 minutes.

[0017] Specifically, in step 1), 10 mg to 500 mg of MnSO 4 ·H 2 O and 54 mg ~ 2.7 g KMnO 4 Mix in 5-30 mL of deionized water; stir magnetically at 30° C. for 30-60 minutes to form a uniform solution; heat in an oven to 120-200° C. and maintain for 8-16 hours; wash by centrifugation with water and anhydrous ethanol for 3-5 times respectively; place the product in a vacuum drying oven at 60-100° C. and dry for 6-12 hours; and calcine at 280-330° C. for 6-9 hours.

[0018] Further, in step 1), β-MnO with different crystal structures 2 The preparation method is: 16mg~1.69g MnSO 4 ·H 2 O and 22.8mg~2.28g(NH 4 ) 2 S 2 O 8 Mix in 5-80 mL of distilled water, then stir magnetically for 30-60 minutes to form a uniform solution, heat to 120-200° C. in an oven and keep for 8-16 hours; wash by centrifugation with water and anhydrous ethanol for 3-5 times respectively; place the product in a vacuum drying oven at 60-100° C. and dry for 6-12 hours; react at 130-160° C. for 8-12 hours.

[0019] Specifically, in step 2), 0.5 g to 5 g of urea or melamine is placed in a ceramic crucible (the amount of urea or melamine does not exceed half the volume of the crucible), the crucible lid is covered, the outer periphery of the crucible is wrapped with aluminum foil, and the crucible is placed in a muffle furnace for calcination. Urea or melamine is heated from room temperature to 500 to 550° C. at a heating rate of 3 to 8° C. / min, calcined at a constant temperature of 500 to 550° C. for 1.5 to 2.5 hours, and then naturally cooled to room temperature. Finally, the light yellow solid formed by calcining and decomposing urea or melamine is ground into powder by agate.

[0020] Specifically, in step 3), sodium tungstate or ammonium tungstate and urea can be mixed by physical mechanical mixing, or mixed in 5-80 mL of distilled water, and then magnetically stirred for 30-60 minutes to form a uniform solution, which is heated to 120-200° C. in an oven and maintained for 8-16 hours.

[0021] Furthermore, in step 3), the mass ratio of the precursor material sodium tungstate or ammonium tungstate to urea is 0.05 to 0.35.

[0022] Furthermore, in step 5), the final composite material has two loading methods, one is to dry the stirred material at 120-200°C for 8-16 hours, and then evenly apply the powder on the glass fiber filter membrane, and the second is to pour the material directly into the groove folded into the glass fiber filter membrane in the solution state without drying, put it into the continuous flow photocatalytic reactor, and blow it with clean air until there is no obvious water droplet attached. This method can make the material evenly loaded on the glass fiber filter membrane, effectively improving the problem of uneven manual powder coating.

[0023] Furthermore, in step 5), the bottom area of ​​the glass fiber filter membrane groove is 0.02 to 0.2 m 2 The clean air purge flow rate is 0.1~5L / min, and the purge form is an external mechanical device (manual fan, hair dryer) or a continuous flow pipeline system.

[0024] The present invention also provides PA / CN-WO prepared by the above preparation method 3 @δ-MnO 2 Composite photocatalytic materials.

[0025] The present invention also provides the above PA / CN-WO 3 @δ-MnO 2 An example of the application of a continuous flow system in which composite photocatalytic materials are uniformly loaded on glass fiber filter paper.

[0026] The present invention also provides the above PA / CN-WO 3 @δ-MnO 2The application of composite photocatalytic materials in the selective removal of gaseous aldehydes in a specific place such as a dining place.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1) PA / CN-WO of the present invention 3 @δ-MnO 2 The composite photocatalytic material introduces an in-situ water layer (self-wetting layer) on the catalyst by introducing hygroscopic periodic acid (PA) to enhance the photocatalytic removal of hydrophilic VOCs in the air. 3 @@δ-MnO 2 A unique three-phase (air / water / CWM) system is formed on the surface of the CWM. The in-situ formed water layer can selectively concentrate hydrophilic VOCs.

[0029] 2) PA / CN-WO of the present invention 3 @δ-MnO 2 The relatively negative conduction band (CB) position of the composite photocatalyst is thermodynamically capable of reducing O 2 Formation O 2 - Superoxide radicals, as key reactive oxygen species in aldehyde removal, are selectively generated, which helps to further purify gaseous aldehydes.

[0030] 3) PA / CN-WO of the present invention 3 @δ-MnO 2 Composite photocatalytic materials can achieve the application purpose of more economical, efficient and selective degradation of low-concentration gaseous aldehydes in specific indoor environments (dining places), solving the technical defect that existing photocatalytic materials cannot selectively degrade single pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 PA / CN-WO provided by the embodiment of the present invention 3 @δ-MnO 2 Flow chart of preparation of composite photocatalytic materials;

[0032] Figure 2 is a schematic diagram of a glass fiber filter membrane groove provided by an embodiment of the present invention;

[0033] Figure 3 PA / CN-WO provided by the embodiment of the present invention 3 @δ-MnO 2 Schematic diagram of composite photocatalytic material loading;

[0034] Figure 4 PA / CN-WO provided by the embodiment of the present invention 3@δ-MnO 2 Diagram of continuous flow system for composite photocatalytic material performance testing;

[0035] Figure 5 The δ-MnO provided by the embodiment of the present invention 2 , WO 3 、CN、CN-WO 3 、CN-WO 3 @δ-MnO 2 Test results of acetaldehyde removal performance of composite photocatalytic materials.

[0036] Figure 6 The PA / δ-MnO provided in the embodiment of the present invention 2 、PA / WO 3 、PA / CN、PA / CN-WO 3 、PA / CN-WO 3 @δ-MnO 2 Test results of acetaldehyde removal performance of composite photocatalytic materials. DETAILED DESCRIPTION

[0037] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.

[0038] The present invention mainly obtains δ-MnO by calcining the precursor material at high temperature. 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 Composite materials.

[0039] The implementation manner of the present invention is further described below in conjunction with specific examples.

[0040] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared according to conventional methods in the art.

[0041] Example 1

[0042] PA / CN-WO in this embodiment 3 @δ-MnO 2 The preparation and loading method of the composite photocatalytic material comprises the following steps:

[0043] 1)δ-MnO 2 In the preparation step, 10 mg to 500 mg of MnSO 4 ·H 2 O and 54 mg ~ 2.7 g KMnO 4 Mix in 5-30 mL of deionized water; stir magnetically at 30° C. for 30-60 minutes to form a uniform solution; heat in an oven to 120-200° C. and maintain for 8-16 hours; wash by centrifugation with water and anhydrous ethanol for 3-5 times respectively; place the product in a vacuum drying oven at 60-100° C. and dry for 6-12 hours; and calcine at 280-330° C. for 6-9 hours.

[0044] 2) In the preparation of graphite phase carbon nitride, 0.5g to 5g of urea or melamine is placed in a ceramic crucible (the amount of urea or melamine does not exceed half the volume of the crucible), the crucible lid is covered and the outer periphery of the crucible is wrapped with aluminum foil and placed in a muffle furnace for calcination. Urea or melamine is heated from room temperature to 500-550°C at a heating rate of 3-8°C / min, calcined at a constant temperature of 500-550°C for 1.5-2.5h, and then naturally cooled to room temperature. Finally, the light yellow solid formed by the calcination and decomposition of urea or melamine is ground into powder by agate.

[0045] 3) CN-WO 3 In the preparation steps of the composite material, sodium tungstate or ammonium tungstate is physically and mechanically mixed with urea, or mixed in 5-80 mL of distilled water, and then magnetically stirred for 30-60 minutes to form a uniform solution, which is heated to 120-200° C. in an oven and maintained for 8-16 hours.

[0046] 4) CN-WO 3 @δ-MnO 2 In the preparation step of the composite material, 70 mg to 3.5 g CN-WO 3 , 54mg~2.7gKMnO 4 10mg~500mg MnSO 4 ·H 2 O is mixed in 5-30 mL of deionized water, and magnetically stirred at 30° C. for 60-90 minutes; dried at 120-200° C. for 8-16 hours; washed by centrifugation with water and anhydrous ethanol for 3-5 times respectively; the product is placed in a vacuum drying oven at 60-100° C. for 12-14 hours; the product is heated from room temperature to 320-370° C. at a heating rate of 9-11° C. / min, and the temperature is maintained for calcination for 2.54 hours.

[0047] 5) PA / CN-WO 3 @δ-MnO 2In the preparation step of the composite photocatalytic material, 10 mg to 0.25 g of CN-WO 3 @δ-MnO 2 Add 1-10 ml of 4-10 wt% PA solution and 5-30 mL of deionized water, and stir magnetically at 30° C. for 60-90 minutes.

[0048] 6) The loading method of the composite photocatalytic material is: when the composite material is in a solution state, it is directly poured into the groove formed by the folded glass fiber filter membrane (see the attached groove structure). Figure 1 ), put it into a continuous flow photocatalytic reactor and blow it with clean air until there is no obvious water droplet attached. See the attached material loading diagram after blowing out water vapor. Figure 3 This method can make the material evenly loaded on the glass fiber filter membrane, effectively improving the problem of uneven artificial powder coating.

[0049] Example 2

[0050] PA / CN-WO of Example 2 3 @δ-MnO 2 The preparation method of the composite photocatalytic material is basically the same as that of Example 1, except that the loading method in step 6) is changed to drying the stirred material at 120-200° C. for 8-16 hours, and then evenly coating the powder on the glass fiber filter membrane.

[0051] Example 3

[0052] The δ-MnO of Example 3 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 The preparation method of the composite material is basically the same as that of Example 1, except that 1 to 10 ml of 4 to 10 wt % PA solution is added in step 1), step 2) and step 3).

[0053] Example 4

[0054] The δ-MnO of Example 4 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 The preparation method of the composite material is basically the same as that of Example 1, except that step 7) WO 3Preparation of materials: 10 mg to 0.5 g of precursor material sodium tungstate was calcined at 520 to 570°C for 3 to 6 hours. 1 to 10 ml of 4 to 10 wt% PA solution and 5 to 30 mL of deionized water were added, and magnetic stirring was performed at 30°C for 60 to 90 minutes.

[0055] For further information, see Appendix Figure 1 , the δ-MnO in each example is given 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 Flow chart of composite material preparation.

[0056] Further, attend the Figure 2 , the δ-MnO in each example is given 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 Schematic diagram of the glass fiber filter grooves required for composite material loading.

[0057] Further, attend the Figure 3 , the δ-MnO in each example is given 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 Schematic diagram of the loading of composite materials after purging water vapor. It is proved that this method can make the material evenly loaded on the glass fiber filter membrane, effectively improving the problem of uneven artificial powder coating.

[0058] Further, attend the Figure 4 , the δ-MnO in each example is given 2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 Diagram of a continuous flow system for composite material performance testing.

[0059] Further, attend the Figure 5 , the δ-MnO in each example is given2 , graphite carbon nitride, CN-WO 3 Composite materials, CN-WO 3 @δ-MnO 2 Composite materials, PA / CN-WO 3 @δ-MnO 2 The test results of acetaldehyde removal performance of composite materials. In the control group without PA loading, CN-WO 3 @δ-MnO 2 It showed the best catalytic performance, increasing the degradation rate of low concentration (10ppm) acetaldehyde from 20.8% to 45.8% under 365nm ultraviolet light. The best single type catalyst for degrading acetaldehyde at low concentration at room temperature was δ-MnO 2 , which is consistent with the order of degradation effects at high concentrations reported in the literature. 2 Introducing CN-WO 3 When the system was used, the degradation rate of low-concentration acetaldehyde increased from 27.9% to 45.8%.

[0060] For further information, see Appendix Figure 6 , PA / δ-MnO in each example is given 2 、PA / graphite carbon nitride、PA / WO 3 、PA / CN-WO 3 Composite materials, PA / CN-WO 3 @δ-MnO 2 The test results of the composite material's acetaldehyde removal performance are shown in Figure 2. In the PA-loaded material comparison group, the addition of PA significantly improved the δ-MnO 2 , WO 3 、CN、CN-WO 3 、CN-WO 3 @δ-MnO 2 The photocatalytic activity of PA / CN-WO 3 @δ-MnO 2 Shows the highest PCD activity. PA / CN-WO 3 @δ-MnO 2 It showed the highest PCD activity, and the degradation rate of low concentration (10 ppm) acetaldehyde at room temperature increased from 45.8% to 68% before and after the addition of PA.

[0061] From the above, it can be seen that the PA / CN-WO of the present invention 3 @δ-MnO 2 Composite photocatalytic materials can achieve the application purpose of more economical, efficient and selective degradation of low-concentration gaseous aldehydes in specific indoor environments (dining places), solving the technical defects of existing photocatalytic materials such as low photodegradation efficiency of single catalysts, uneven loading and inability to selectively degrade a single species.

Claims

1. A method for preparing, loading and applying a PA / CN-WO3@δ-MnO2 composite photocatalytic material, characterized in that: Includes steps: 1) δ-MnO2, g-C3N4, and WO3 with the best crystal structure for removing aldehydes were prepared by high-temperature calcination of manganese dioxide precursor materials (MnSO4·H2O, KMnO4), graphite phase carbon nitride precursor materials (urea), and tungsten trioxide precursor (Na2WO4). 2) The precursor materials of δ-MnO2, g-C3N4 and WO3 are stirred in deionized water, washed, dried, calcined at high temperature, and then hygroscopic periodic acid (PA) is added to obtain the PA / CN-WO3@δ-MnO2 composite photocatalytic material solution of the present invention. 3) When in solution state, pour it directly into the groove formed by folding the glass fiber filter membrane, put it into the continuous flow photocatalytic reactor, and blow it with clean air until there are no obvious water droplets attached.

2. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1 is characterized in that: The hygroscopic periodic acid (PA) loading in step 2) is 1 to 10 ml of a 4 to 10 wt % PA solution.

3. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1 is characterized in that: The specific steps of high temperature calcination of the manganese dioxide precursor material described in step 1) are: calcining 10 mg to 500 mg of MnSO4·H2O and 54 mg to 2.7 g of KMnO4 at 280 to 330° C. for 6 to 9 hours.

4. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1, characterized in that: The specific steps of high temperature calcination of the graphite phase carbon nitride precursor material (urea) described in step 1) are: heating urea or melamine from room temperature to 500-550°C at a heating rate of 3-8°C / min, and calcining at a constant temperature of 500-550°C for 1.5-2.5h.

5. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1, characterized in that: In step 2), the mass ratio of the precursor material sodium tungstate or ammonium tungstate to urea is 0.05 to 0.

35.

6. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1, characterized in that: The high temperature calcination in step 2) is to raise the temperature of the product from room temperature to 320-370° C. at a heating rate of 9-11° C. / min, and maintain the temperature for calcination for 2.5-4 hours.

7. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1, characterized in that: In step 3), the bottom area of ​​the glass fiber filter groove is 0.02 to 0.2 m 2 The clean air purge flow rate is 0.1~5L / min, and the purge form is an external mechanical device (manual fan, hair dryer) or a continuous flow pipeline system.

8. The preparation, loading and application method of the PA / CN-WO3@δ-MnO2 composite photocatalytic material according to claim 1, characterized in that Used for the removal of low concentration gaseous aldehydes (such as formaldehyde, acetaldehyde, propionaldehyde, acrolein) of 5ppm to 50ppm.